Case Study: Local Anesthetic Toxicity After Bier Block. Was intralipid Therapy the Correct Remedy - Dawood Nasir; Babatunde Ogunnaike; Charles Whitten (Open Journal of Pain Medicine - Peertechz Publications, 2017)
Introduction: Intralipid therapy is recommended for patients with local anesthetics like Bupivacaine, but it is not advisable for patients with short acting local anesthetic toxicity like Lidocaine. Presentation of case: 42 years old healthy female was brought to Operating room for release of carpel tunnel syndrome of left hand. It was decided to perform Bier block. After placement of successful Bier block, surgery was completed in twenty minutes and after tourniquet release, pt. noted to have shaking movement. Local anesthetic toxicity was suspected as the tourniquet was released too soon, before the recommended time of forty fi ve minutes. ACLS protocol was initiated providing oxygen to patient and providing assistance on breathing and taking care of airway. Patient initially was confused and agitated. But recovered after few minutes and very soon became awake and alert. She was kept on observation for few hours before being discharged. The question was, could intralipid therapy would have been helpful in patients with lidocaine toxicity. Conclusion: Intralipid therapy may be benefi cial if long acting local anesthetics like Bupivacaine was being used. Bupivacain is also cardio toxic and has a long duration of action. For short acting local  anesthetics or local anesthetic's which are less cardio toxic,following ACLS protocol with symptomatic support may be suffi cient for successful resuscitation. Historical facts: The Bier Block was fi rst introduced by August Bier in 1908 but C. McK. Holmes reintroduced it in 1963.Today, the technique is common as it is economical, it has a rapid recovery, it is reliable and is simple to use.Intravenous regional anesthesia or Bier block anesthesia is an anesthetic technique for surgical procedures on the body's extremities especially the upper extremity where a local anesthetic is injected intravenously. The technique usually involves exsanguination which forces blood out of the extremity,followed be the application of pneumatic tourniquets to safely stop blood fl ow. The anesthetic agent is introduced into the limb and allowed to set in while tourniquets retain the agent within the desired area. After some time, the tourniquet is depressurized to start back the circulation.